2015
DOI: 10.1002/2014jb011508
|View full text |Cite
|
Sign up to set email alerts
|

Glacial isostatic adjustment in the static gravity field of Fennoscandia

Abstract: In the central part of Fennoscandia, the crust is currently rising, because of the delayed response of the viscous mantle to melting of the Late Pleistocene ice sheet. This process, called Glacial Isostatic Adjustment (GIA), causes a negative anomaly in the present-day static gravity field as isostatic equilibrium has not been reached yet. Several studies have tried to use this anomaly as a constraint on models of GIA, but the uncertainty in crustal and upper mantle structures has not been fully taken into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 44 publications
(76 reference statements)
3
34
0
Order By: Relevance
“…This corroborates our assumption that compensated masses are situated in the region between the LAB and the Moho. The compensation is shown to represent the global gravity observations well in most of the spectral domain (Root et al 2015). The separation between the lithosphere and asthenosphere is obtained from Hamza & Vieira (2012), which is based on global databases of heat flow (Vieira & Hamza 2010) and crustal structure (Laske et al 2013).…”
Section: Gravity-based Model Of the Lithospherementioning
confidence: 99%
See 2 more Smart Citations
“…This corroborates our assumption that compensated masses are situated in the region between the LAB and the Moho. The compensation is shown to represent the global gravity observations well in most of the spectral domain (Root et al 2015). The separation between the lithosphere and asthenosphere is obtained from Hamza & Vieira (2012), which is based on global databases of heat flow (Vieira & Hamza 2010) and crustal structure (Laske et al 2013).…”
Section: Gravity-based Model Of the Lithospherementioning
confidence: 99%
“…Kaban et al 2004;Root et al 2015;Herceg et al 2016). However, due to the intrinsic non-uniqueness of gravity modelling the solutions need to be constrained, which introduces uncertainties in the final model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a reference profile we use VM5a (Peltier and Drummond, 2008), which is an iteration of the VM2 profile that is used in the creation of ICE-5G (Peltier, 2004). As alternative profiles we select profiles that have been shown by Root et al (2015b) to provide a good fit to sea level data, GPS, and GRACE (Gravity Recovery and Climate Experiment) data in Fennoscandia. That study found two viscosity profiles: one with higher viscosities in the upper and lower mantle and one with lower viscosities.…”
Section: Model Inputs: Viscosity and Ice Loadingmentioning
confidence: 99%
“…That study found two viscosity profiles: one with higher viscosities in the upper and lower mantle and one with lower viscosities. The fact that sediment loading is not taken into account to obtain viscosity profiles in Root et al (2015b) will have a minor effect on our results given that three very different viscosity profiles are selected to account for uncertainty in viscosity. Out of those sets we select M8-128-150 and M4-16-80, where the first number denotes the upper mantle viscosity in 10 20 Pa s, the second number denotes the lower mantle viscosity in 10 20 Pa s, and the third number denotes the lithosphere thickness in kilometers.…”
Section: Model Inputs: Viscosity and Ice Loadingmentioning
confidence: 99%